A boundary problem for a single class of third-order equations - Abulov M.O. (Genius Journals, 2022)
The boundary problem for a third-order equation of mixed type in a four-angle region is considered. Using the Galerkin method, under certain conditions, the existence of a weakly generalized solution in Sobolev's space was proved on the coefficients and the right side of the equation. Under the same conditions, the uniqueness of the generalized solution is proved
Keywords: Galerkin method; boundary problem; third-order equation